Fluorescent Proteins: Strong Coupling in Fully Tunable Microcavities Filled with Biologically Produced Fluorescent Proteins (Advanced Optical Materials 1/2017). Issue 1 (January 2017) - Dietrich, Christof P.; Steude, Anja; Schubert, Marcel; Ohmer, Jürgen; Fischer, Utz; Höfling, Sven; Gather, Malte C.
Abstract : Biologically produced fluorescent protein molecules emitting green or red light are mixed and inserted into high quality optical resonators, by C. P. Dietrich, S. Höfling, M. C. Gather, and co‐workers in article number 1600659, to study strong coupling between photons and the excited state of the protein molecule. The mixing ratio and the size of the resonator provide two independent handles for tuning light–matter coupling.